The hurdling on home straight in the women 3000m steeplechase - Maruo, Y. (Scientific Journal of Sport and Performance, 2023)
The 3000m steeplechase is an event in which athletes must clear 28 hurdles and 7 water jumps while competing for the fastest time. In this race, women must clear hurdles set at a height of 0.762 meters, whereas men face hurdles set at a height of 0.914 meters. There is a paucity of research on the 3000m steeplechase compared to other long-distance events. This study aimed to clarify the characteristics of hurdle clearance for the 3000m steeplechase. Investigating how to clear the hurdles on the home straight could significantly enhance race strategies and performance. Data were collected from the women`s 3000m steeplechase races at Kanto intercollegiate race. 15 women`s performances were analyzed. The 3000m steeplechase races were recorded by video camera. All jumps from participants were digitized using Kinovea (version 0.9.3). I focused on variables of three steps related to the three steps around hurdles, and comparisons were made among each lap. In terms of total clearance speed, we observed that lap 4 had a lower speed than lap 3, and lap 7 had a higher speed than lap 4. Before the increase in speed at the hurdle, there was an increase in the length of three steps in lap 7. Athletes in the final lap took off from a longer distance and achieved a faster clearance speed. The step frequency before hurdle clearance was higher in lap1 and lap2 than in lap4, lap5, lap6, and lap7. In addition, step frequency after hurdle clearance did not differ among laps and was lower than before hurdle clearance. Fatigue might be a contributing factor to this decline in step frequency before hurdle clearance. It would be advantageous for athletes to consciously increase their step frequency when approaching the next hurdle. The present study provided practical evidence for hurdle clearance of 3000m steeplechase.